Constitutional Amendment by Stealth - Albert, Richard (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2015)
Constitutional amendment ordinarily channels public deliberation through formal, transparent, and predictable procedures designed to express the informed aggregated choices of political, popular, and institutional actors. Yet the Government of Canada’s proposed senator selection reforms concealed a democratically problematic strategy to innovate an informal, obscure, and irregular method of constitutional change: constitutional amendment by stealth. There are three distinguishing features of constitutional amendment by stealth—distinctions that make stealth amendment stand apart from other types of informal constitutional change: the circumvention of formal amendment rules, the intentional creation of a convention, and the twinned consequences of both promoting and weakening democracy. Constitutional amendment by stealth occurs where political actors consciously establish a new democratic practice whose repetition is intended to compel their successors into compliance. Over time, this practice matures into an unwritten constitutional convention, and consequently becomes informally entrenched in the constitution, though without the democratic legitimacy we commonly associate with an amendment. In this article, I theorize constitutional amendment by stealth from legal, theoretical, and comparative perspectives, and consider its consequences for the rule of law.